2005
DOI: 10.1007/s00432-004-0632-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5 alpha reductase inhibitors on androgen-dependent human prostatic carcinoma cells

Abstract: Considering that 5alphaR1 (responsible primarily for androgenic catabolism) is mostly expressed in epithelial cells and that 5alphaR2 (responsible for local DHT synthesis and release) is expressed in the stromal cells (which provides several paracrine growth factors and DHT itself to the epithelial cells), our experiments suggest that the inhibition of both 5alphaR1 and 5alphaR2 by MK386 and MK906, respectively, may have therapeutic potential in order to reduce the growth and progression of human prostatic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…There were no significant changes in the percentages of treated primary responder and nonresponder epithelial cells that progressed to G 2 M-phase of the cell cycle after treatment for 24 hours. In a recent study, Festuccia et al 31 showed that dual inhibition of both 5 ␣-reductase enzymes by MK906 (Finasteride) and MK386 in primary cultures of prostate cancer cells (that contained both fibroblast/stromal cells and epithelial cells) induced several morphologic changes and demonstrated growth inhibition. In addition, inhibition of growth also was observed in the same study in LNCaP cells that were cocultured with prostate cancer fibroblasts and in LNCaP cells that were cocultured with fibroblasts or stroma derived from BPH specimens.…”
Section: 12mentioning
confidence: 99%
“…There were no significant changes in the percentages of treated primary responder and nonresponder epithelial cells that progressed to G 2 M-phase of the cell cycle after treatment for 24 hours. In a recent study, Festuccia et al 31 showed that dual inhibition of both 5 ␣-reductase enzymes by MK906 (Finasteride) and MK386 in primary cultures of prostate cancer cells (that contained both fibroblast/stromal cells and epithelial cells) induced several morphologic changes and demonstrated growth inhibition. In addition, inhibition of growth also was observed in the same study in LNCaP cells that were cocultured with prostate cancer fibroblasts and in LNCaP cells that were cocultured with fibroblasts or stroma derived from BPH specimens.…”
Section: 12mentioning
confidence: 99%
“…This might be expected for transit amplifying cells, however, is in contrast to a few other published studies. Festuccia et al for instance found moderate high levels of AR, PSA and KlK2 in outgrowing cells from prostate tissue clumps (16) and a decreased cell proliferation upon treatment with 5-·-reductase inhibitors (17). Moreover, bicalutamide was shown to decrease cell viability in a dosedependent manner (18).…”
Section: Discussionmentioning
confidence: 99%
“…8 The application of inhibitors of the 5a-R1 and 5a-R2 isoforms in cultures of primary prostate cancer decreased the cell proliferation dose-dependently through auto-or paracrine mechanisms. 53 When patients are treated with Dutasteride 6-10 weeks before radical prostatectomy the intraprostatic DHT 5a-Reductase inhibitor treatment J Dörsam and J Altwein was reduced by 97% and apoptosis was augmented possibly indicating tumor regression. 52 The effect of androgen deprivation on prostate cancer tissue was also investigated.…”
Section: Chemoprevention Of Prostate Cancermentioning
confidence: 99%